Cluster Analysis Of Marine Toll Service Area To Minimize Price Disparity To Inprove The Economy Of The East Indonesian Region In The Era Of The Covid-19 Pandemic - Kusuma, Lalu Wijaya Nata (Journal of Innovation and Applied Technology, 2022)
High price disparity is an economic problem that causes the welfare level of the population to be low. The government through the Sea Highway program tries to reduce price disparities through subsidized and scheduled sea transportation to serve several ports in Indonesia, one of which is in the province of Riau Islands. The Strait of Lampa Port is one of the marine transportation nodes which is a stopover point for Sea Toll boats on the T-3 route serving Natuna Regency. This port has the status of a regional feeder port with the hinterland area of Natuna Regency with Ranai as the district capital. This study aims to provide input related to the clustering of the Marine Highway program in Natuna from several perspectives, namely from the potential of regional commodities and infrastructure for Sea Toll services in the Natuna region.